Hubungan Antara Paradigma Lingkungan Baru Dengan Perilaku Tanggung Jawab Lingkungan Siswa - Septika Augis Ulmi Kaan; I Made Putrawan; Mieke Miarsyah (Universitas Negeri Jakarta, 2019)
Responsible environmental behavior is the result of interaction between various factors. One of those factors is the new environmental paradigm. This study aims to determine the relation between the new environmental paradigm to responsible environmental behavior in high school students in Jakarta. The research was conducted at Jakarta State Senior High School 53 in the first semester of the 2017/2018 Academic Year. The method used is a survey method with correlational techniques. The sample used was 89 students of class XI MIA random sampling. Data was collected using new environmental paradigm instruments and responsible environmental behavior instruments. Data analysis was done by simple linear regression test to measure the magnitude of the relation using the Pearson Product Moment formula at the 5% significance level. The results of the study show that there is a positive and significant the relation between the new environmental paradigm to responsible environmental behavior. The correlation coefficient of this study is 0.276. The contribution of the new environmental paradigm variable to responsible environmental behavior variable is 7.6%. Therefore, the environmental paradigm has a role in improving student's responsible environmental behavior. Keywords: new environmental paradigm, responsible environmental behavior, students.